Weather-related Employment Subsidies as a Remedy for Seasonal Unemployment? Evidence from Germany - Arntz, Melanie; Wilke, Ralf A. (Labour, 2012)
Many European countries try to reduce seasonal unemployment by subsidizing short-time employment during the winter period. Despite such costly efforts, pronounced seasonal unemployment patterns continue to exist. This puts doubts on the effectiveness of such policy interventions. This paper provides a first empirical assessment of the effectiveness of different subsidy schemes by exploiting the institutional variation in a German subsidy scheme that applies to the construction sector and the variation in local weather and business cycle conditions across 20 years. The findings confirm that generous short-time subsidies reduce individual lay-off probabilities in the case of poor weather conditions. However, the link between weather conditions and seasonal lay-offs is much less strong than expected, making planned capacity reductions the main suspect for causing seasonality in unemployment patterns. © 2012 CEIS, Fondazione Giacomo Brodolini and Blackwell Publishing Ltd.
CRIS-Team Scopus Importer:2025-02-03
Keywords: Erfolgskontrolle; saisonale Arbeitslosigkeit; Schlechtwettergeld; Wintergeld; Lohnsubvention; Arbeitslosigkeitsbekämpfung; Baugewerbe; Beschäftigungseffekte; Entlassungen; IAB-Regionalstichprobe; Winterbauförderung; Erfolgskontrolle; Westdeutschland; Bundesrepublik Deutschland